THE IMPORTANCE OF ALEXANDER FEINBERG’S WORKS IN UZBEK LITERATURE ("Conference on Universal Science Research 2023", 2024)
This article provides detailed information about Alexander Feinberg, who, despite being a Russian-speaker, was able to find a place in the heart of the Uzbek nation. Covering many aspects of Feinberg's literary heritage, highlighting its importance at the same time, it is intended to inculcate the main ideas of the poet's work to the readers. His writings come to the hands of Uzbek readers, he translated rare examples of Uzbek literature into Russian, that is, his translation skills are also interpreted. Feinberg's works are promoted among young artists in order to spread it more widely.